What Happens to the State in Conflict?: Political Analysis as a Tool for Planning Humanitarian Assistance - Cliffe, Lionel; Luckham, Robin (Disasters, 2000)
It is now part of received wisdom that humanitarian assistance in conflict and post-conflict situations may be ineffective or even counterproductive in the absence of an informed understanding of the broader political context in which so-called ‘complex political emergencies’ (CPEs) occur. Though recognising that specific cases have to be understood in their own terms, this article offers a framework for incorporating political analysis in policy design. It is based on a programme of research on a number of countries in Africa and Asia over the last four years. It argues that the starting-point should be an analysis of crises of authority within contemporary nation-states which convert conflict (a feature of all political systems) into violent conflict; of how such conflict may in turn generate more problems for, or even destroy, the state; of the deep-rooted political, institutional and developmental legacies of political violence; and of the difficulties that complicate the restoration of legitimate and effective systems of governance after the ‘termination’ of conflict. It then lists a series of questions which such an analysis would need to ask — less in order to provide a comprehensive check-list than to uncover underlying political processes and links. It is hoped these may be used not only to understand the political dynamics of emergencies, but also to identify what kinds of policy action should and should not be given priority by practitioners.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; governance / governação